Are You “In the Zone” Or “Disconnected”? : An Investigation of Flow, Dissociative Absorption and Their Adaptive and Maladaptive Correlates - Zadik, Michal; Bregman-Hai, Noa; Soffer-Dudek, Nirit (Journal of Anomalous Experience and Cognition, 2022)
Objective: The terms dissociative absorption and flow describe tendencies to experience immersive consciousness states, yet dissociation is sometimes considered maladaptive whereas flow is typically considered to be adaptive. We explored their trait and state associations with psychopathology, game task performance, and mood, and examined the hypothesized moderation effect of self-efficacy. Method: In the present study, 303 undergraduates completed trait questionnaires and 63 high/low absorbers reported their state before and after an immersive task (“Tetris”). Task performance was also assessed. Results: We found that flow was distinguishable from dissociation but was inconsistent; two of its components (“transformation of time” (ToT) and “merging of action and awareness” (MoAA)) were positively associated with dissociation and psychopathology, and, unlike other flow components, were unrelated to enhanced task performance. Although the trait associations of ToT and MoAA with psychopathology were not dependent on self-efficacy levels, trait dissociation was more strongly related to psychopathology under low self-efficacy. In the state phase, state immersion (both ToT and dissociative absorption) was associated with mood improvement, especially under low self-efficacy. Conclusion: Our results prompt us to question the validity of flow as a cohesive construct, as measured by the Dispositional Flow Scale-2. Immersive experiences, including ToT and dissociative absorption, led to short-term mood improvement in the state phase but, considering their trait associations with psychopathology, engaging in them excessively may be maladaptive in the long term.